Handbook of self and identity - Leary, Mark R.; Tangney, June Price (The Guilford Press, a division of Guilford Publications, Inc., 2005)
The self has emerged as a central construct in many domains of behavioral and social science. This state-of-the-science volume brings together an array of leading authorities to provide the first comprehensive review of theory and research in this burgeoning area. Organized into five sections, chapters address the content, structure, and organization of the self processes related to agency, regulation, and self-control self-evaluation and self-related motivation and emotion interpersonal and cultural aspects of self and identity and self-development across evolutionary time and the life span. Also examined are ways that the development of the self sometimes goes awry, resulting in emotional and behavioral problems. Shedding light on a key dimension of human experience, the [ital]Handbook[/ital] is a definitive reference and text.